Gelled Lyotropic Liquid Crystals - Xu, Yang; Laupheimer, Michaela; Preisig, Natalie; Sottmann, Thomas; Schmidt, Claudia; Stubenrauch, Cosima (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Use of Eutectic Mixtures for Preparation of Monolithic Carbons with CO2-Adsorption and Gas-Separation Capabilities - Lopez Salas, Nieves; Jardim, E. O.; Silvestre-Albero, A.; Gutiérrez, M. C.; Ferrer, M. L.; Rodríguez-Reinoso, F.; Silvestre-Albero, J.; del Monte, F. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Mechanistic Studies of Silica Polymerization from Supersaturated Aqueous Solutions by Means of Time-Resolved Light Scattering - Kley, M.; Kempter, A.; Boyko, V.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Structural Evolution in the Isotropic Channel of a Water–Nonionic Surfactant System That Has a Disconnected Lamellar Phase: A 1H NMR Self-Diffusion Study - Stubenrauch, Cosima; Kleinschmidt, Felix; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Impact of Sodium Polyacrylate on the Amorphous Calcium Carbonate Formation from Supersaturated Solution - Liu, J.; Pancera, S.; Boyko, V.; Gummel, J.; Nayuk, R.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Imaging of the Ferroelectric Domain Structures by Confocal Raman Spectroscopy - Berth, Gerhard; Hahn, Wjatscheslaw; Wiedemeier, Volker; Zrenner, Artur; Sanna, Simone; Schmidt, Wolf Gero (Ferroelectrics)
Confocal Raman spectroscopy was performed as an archetype imaging method to study the ferroelectric domain structure of periodically poled lithium niobate. More precisely, the linkage out of spatial resolution and spectral information proved itself as very useful. Here a specific modulation of the Raman lines by the local variation of polarity and a non-symmetric measuring-signal across the domain structure were found, which allows for imaging of domain boundaries as well as oppositely orientated domains. The high potential of this method is demonstrated by the visualization of the ferroelectric domain structures based on various phonon modes.
Keywords: Raman spectroscopy; ferroelectric domains; LiNbO3; confocal imaging

Molecular Recognition with 2,4-Diaminotriazine-Functionalized Colloids - Bayer, Frank M.; Tang, Mingxue; Michels, Rolf; Schmidt, Claudia; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Molecular Recognition with 2,4-Diaminotriazine-Functionalized Colloids - Bayer, Frank M.; Tang, Mingxue; Michels, Rolf; Schmidt, Claudia; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Exposure of [MnIII6CrIII]3+ single-molecule magnets to soft X-rays: The effect of the counterions on radiation stability - Helmstedt, Andreas; Sacher, Marc; Gryzia, Aaron; Harder, Alexander; Brechling, Armin; Müller, Norbert; Heinzmann, Ulrich; Hoeke, Veronika; Krickemeyer, Erich; Glaser, Thorsten; Bouvron, Samuel; Fonin, Mikhail (Journal of Electron Spectroscopy and Related Phenomena)
Keywords: Physical and Theoretical Chemistry; Spectroscopy; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Radiation; Electronic; Optical and Magnetic Materials

Size Determination of Shear-Induced Multilamellar Vesicles by Rheo-NMR Spectroscopy - Medronho, B.; Schmidt, Claudia; Olsson, U.; Miguel, M. G. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced Defect Formation in a Nonionic Lamellar Phase - Medronho, B.; Rodrigues, M.; Miguel, M. G.; Olsson, U.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Evaluation of the Particle Growth of Amorphous Calcium Carbonate in Water by Means of the Porod Invariant from SAXS - Liu, J.; Pancera, S.; Boyko, V.; Shukla, A.; Narayanan, T.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Hydrogen-Bond-Induced Heteroassembly in Binary Colloidal Systems - Bayer, Frank M.; Hiltrop, Karl; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced Transitions between a Planar Lamellar Phase and Multilamellar Vesicles: Continuous versus Discontinuous Transformation - Medronho, B.; Shafaei, S.; Szopko, R.; Miguel, M. G.; Olsson, U.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Analysis of the Nucleation and Growth of Amorphous CaCO3 by Means of Time-Resolved Static Light Scattering - Liu, Jianing; Rieger, Jens; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Structure−Property Relationship in Stimulus-Responsive Bolaamphiphile Hydrogels - Meister, Annette; Bastrop, Martin; Koschoreck, Sven; Garamus, Vasil M.; Sinemus, Thomas; Hempel, Günter; Drescher, Simon; Dobner, Bodo; Richtering, Walter; Huber, Klaus; Blume, Alfred (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Aggregation of a Pseudoisocyanine Chloride in Aqueous NaCl Solution - Herzog, Bernd; Huber, Klaus; Stegemeyer, Horst (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Lyotropic Mesophases Next to Highly Efficient Microemulsions: A 2H NMR Study - Stubenrauch, Cosima; Frank, Christian; Strey, Reinhard; Burgemeister, Daniel; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Model of Polydisperse Wormlike Stars and Its Application to Dyestuff Aggregates - Katzenstein, Armin; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Time-Resolved Recording of Ionic Dyestuff Aggregation by Static Light Scattering - Inglés, Sergio Escudero; Katzenstein, Armin; Schlenker, Wolfgang; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science